Beyond cruelty: Analyzing sexual and gender-based violence as torture and inhuman treatment - Novakovic, Filip (Temida, 2024)
This article delves into the critical intersection of sexual and gender-based violence (SGBV) and the international legal frameworks governing torture and inhuman treatment. SGBV represents one of the most pervasive and devastating violations of human rights worldwide, with women and girls disproportionately affected. It aims to analyze how categorizing SGBV as acts of torture and inhuman treatment under international law can provide a more robust legal framework for addressing these violations, acknowledging the prevalent majority of victims being women and girls. By elucidating the multifaceted nature of SGBV and its impact, and examining legal precedents and jurisprudential developments, the article contributes to the evolving conceptualization of SGBV within the context of torture and inhuman treatment, with a focus on women?s suffering. Moreover, it highlights the practical and symbolic benefits of this categorization, including enhanced legal accountability and increased protection for survivors. The article concludes by emphasizing the urgent need for a unified approach by international stakeholders and policymakers to address SGBV as a distinct and pervasive form of torture and inhuman treatment, contributing to the ongoing discourse on sexual and gender-based violence and offering insights for advancing the protection of vulnerable individuals and marginalized communities on a global scale.